Female Genital Mutilation in Perspective: Black Women and the Politics of Feminism - Olugbemi-Gabriel, Olumide (Àgídìgbo: ABUAD Journal of the Humanities, 2015)
The failure offeminism as conceptualised by the West to accommodate the peculiar experiences of Black/African women, of which female genital mutilation (FGM) is one, has culminated in the production of some Afrocentric strands of feminism which seek to antagonise the universalisation of the experiences of women as conceived by "White Feminism", The efforts of Black women in this regard across the boundaries of location, indicate a vehement rejection of any attempt to force them to accept any foreign imposed "ism" as a gender theory for a whole, Being a signifier of culture, the theoretical framework for deconstructing FGM practices should be located within the milieu of Afrocentric or Afrofriendly feminism. This paper concludes by applauding Third World feminism - an Afrofriendly feminist theory as the most suitable platform for engaging FGM because it recognizes how culture and traditions are instrumental in the oppression of women within national boundaries of Third World space.